Global Trends in Green Finance in the Banking Sector: A Bibliometric Mapping of Past and Future Research Directions - Rusdi Hidayat Nugroho; Indah Respati Kusumasari; Nugraha Kusbianto; Nurhadi Nurhadi; Lusi Kurnia (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: This analysis is a systematic review of green finance in the banking sector, combining information from 193 papers published in 126 journals indexed in Scopus between 2020 and 2025. Objective: To provide a broad reference source for future research and a better understanding of the interaction between banks, environmental protection, climate change, and the 2030 Sustainable Development Goals. The most recent contributions in green banking—mitigation of risk, technology, credit policy, and ethical practices within organizations—are pointed out. Methods: Quantitative analysis based on bibliometric methodology of the Scopus database with search string TITLE-ABS-KEY("green finance") AND TITLE-ABS-KEY("bank" OR "banking"). Data screening followed the PRISMA framework (N₁=312 → N₂=246 → N₃=193). Bibliometric analysis was conducted using R 4.3.2 (Bibliometrix package) and VOSviewer 1.6.20 for keyword co-occurrence, co-authorship, and thematic mapping. Results: The review reveals five influencing factors and four main research thematic fields, addressing (i) what has already been investigated in green finance applied to banks, and (ii) what directions remain unexplored. The paper concludes with a forward-looking agenda to align green finance definitions and measurements across countries, integrate green risk into regulatory frameworks, incorporate it into credit decisions, and use technology to facilitate effective implementation of the emerging global landscape in green finance. Conclusion: Green finance in banking has gone from a conceptual framing to an empirical inquiry structured by laws and the regulatory regime. Research going forward needs to focus on cross-nation comparability, ethical governance of banks, climate-risk assessment in credit decisions, and fintech solutions for green finance channeled through banks—with a focus on developing economies like Indonesia.